2007
DOI: 10.1111/j.1365-2265.2007.02800.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of RET/PTC, TRK and BRAF mutations in preoperative diagnosis of thyroid nodules with indeterminate cytological findings

Abstract: SummaryBackground Fine-needle aspiration biopsy (FNAB) is the primary means to distinguish benign from malignant nodules and select patients for surgery. However, adjunctive diagnostic tests are needed because in 20-40% of cases the FNAB result is uncertain. Objective We investigated whether a search for the oncogenes RET/PTC, TRK and BRAF V600E in thyroid aspirates could refine an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 19 publications
1
90
0
3
Order By: Relevance
“…Recent studies reported that the BRAF mutation is a highly accurate marker of malignancy for thyroid nodules sampled by FNAB [205][206][207][208][209]. However, the most frequent diagnostic problems in FNAB samples are indeterminate follicular tumors and suspicion of malignancy according to the Bethesda system.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…Recent studies reported that the BRAF mutation is a highly accurate marker of malignancy for thyroid nodules sampled by FNAB [205][206][207][208][209]. However, the most frequent diagnostic problems in FNAB samples are indeterminate follicular tumors and suspicion of malignancy according to the Bethesda system.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…A number of groups have suggested molecular markers to assist in the diagnosis of papillary thyroid carcinoma from fine-needle aspiration specimens. 40,41 Sapio et al 42 recently proposed detection of ret/PTC, TRK and BRAF (V600E) in fine-needle aspiration specimens as a diagnostic adjunctive tool in the evaluation of thyroid nodules. They found that the discovery of oncogenes in fineneedle aspiration specimens suspicious for malignancy guided the extent of surgical resection, changing the surgery from diagnostic to therapeutic in five cases.…”
Section: Applicationsmentioning
confidence: 99%
“…We used the forward primer for H4 gene and the reverse primer for the tyrosine kinase domain of RET (Supplementary Table S1). PCR conditions were performed according to a previously described protocol (Sapio et al 2007). Afterwards, 10 ml of the PCR product were analyzed by electrophoresis in a 1.5% agarose gel.…”
Section: Human Ptc Samplesmentioning
confidence: 99%